Design of PSO-Based Optimal/Tunable PID Fuzzy Logic Controller Using FPGA - Obaid, Zeyad Assi; Salman, Saad Abd Almageed; Ali, Hazem I.; Sulaiman, Nasri; Marhaban, M. H.; Hamidon, M. N. (IntechOpen, 2011)
None